Polemik Eskalasi Penjaringan Panwascam Menjelang Pemilu Serentak 2024 Di Bawaslu Kota Gorontalo - Mulya Ningsi Katili (Journal of Cross Knowledge, 2023)
2024 is the year that the Indonesian people have been waiting for because in that year there will be two major events to be held, namely the democratic party for the general election of President/Vice President and the Election of Regional Heads. The General Elections Supervisory Agency and the General Election Commission or abbreviated as KPU, are some of the state institutions that organize the event. Election organizers and local elections are required to realize the implementation of the 2024 General Election and Regional Head Elections that are clean and with integrity, based on the principles of LUBER (Direct, Public, Free, Confidential) and JURDIL (Honest and Fair). In realizing this, of course, cannot be separated from the readiness of human resources from the two state institutions in carrying out their duties and functions. The Gorontalo City Bawaslu Human Resources are superior and multitalented human resources, because individuals who work in these state institutions are able to do two or more tasks at the same time with unlimited working time. Human resources have an important role for the sustainability of an organization of state institutions. It is undeniable that in a state institution there is a lack of human resource capacity in carrying out its duties and functions in its implementation. Therefore, the Gorontalo City Bawaslu should have escalated the selection of the Panwascam ahead of the upcoming 2024 simultaneous elections. Even though there was a polemic in the selection process some time ago, everything was handled well by the Gorontalo City Bawaslu.